2010
DOI: 10.1016/j.physb.2009.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Infrared study of the phonon modes in PrMnO3 and CaMnO3

Abstract: The infrared (IR) reflectivity spectra of orthorhombic manganese perovskites PrMnO3 and CaMnO3 are studied in the frequency range of optical phonon modes at temperatures varying from 300 to 4 K. The IR phonon spectra of these two materials are analyzed by a fitting procedure based on a Lorentz model, and assigned to definite vibrational modes of P nma structures by comparison with the results of lattice dynamical calculations. The calculations have been performed in the framework of a shell model using short r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 59 publications
3
14
0
Order By: Relevance
“…In addition, the obtained vibrational energies E (A) vib (T ) basically reveal the expected temperature trends, i.e., an almost temperature-independent behavior characterized by the zero-point phonon energy for T < D 2 ∼ 150 K and a linear increase with a slope of roughly kT at higher temperatures indicating thermal phonon broadening of the polaron absorption bands. The deviation from this temperature trend for x = 0.2, i.e., the decrease of E (A) vib (T ) at low temperature may be attributed to the presence of the ferromagnetic insulating (FMI) phase at T < 180 K. Moreover, the vibrational energies governing small polaron hopping transfer at T = 80 K in hole doped PCMO (x 0.5), E (A) vib = 1 2 ω (A) 0 ∼ 18-30 meV, are roughly consistent with a band of vibrational Mn-O-Mn tilt modes found in the energy range of ω 0 ∼ 30-50 meV in PCMO at various doping levels [18,42,43,45]. These modes change the octahedral tilting angle between nearest neighbor sites and, thus, may facilitate the intersite hopping transfer.…”
Section: Intraband Polaron Hoppingsupporting
confidence: 74%
“…In addition, the obtained vibrational energies E (A) vib (T ) basically reveal the expected temperature trends, i.e., an almost temperature-independent behavior characterized by the zero-point phonon energy for T < D 2 ∼ 150 K and a linear increase with a slope of roughly kT at higher temperatures indicating thermal phonon broadening of the polaron absorption bands. The deviation from this temperature trend for x = 0.2, i.e., the decrease of E (A) vib (T ) at low temperature may be attributed to the presence of the ferromagnetic insulating (FMI) phase at T < 180 K. Moreover, the vibrational energies governing small polaron hopping transfer at T = 80 K in hole doped PCMO (x 0.5), E (A) vib = 1 2 ω (A) 0 ∼ 18-30 meV, are roughly consistent with a band of vibrational Mn-O-Mn tilt modes found in the energy range of ω 0 ∼ 30-50 meV in PCMO at various doping levels [18,42,43,45]. These modes change the octahedral tilting angle between nearest neighbor sites and, thus, may facilitate the intersite hopping transfer.…”
Section: Intraband Polaron Hoppingsupporting
confidence: 74%
“…Observed Raman and IR bands for CaGa 2 O 4 , Ca 2 GeO 4 , CaIn 2 O 4 , CaSnO 3 and the bands assignment Modes involving the displacements of the apical oxygen and Ca 2+ atoms[46] …”
mentioning
confidence: 89%
“…The calculated Raman frequencies for CaMnO 3 , on which the mode assignment is based, is also recalled. For comparison, the results of the shell model calculations for CaMnO 3 by Sopracase et al [50] are also indicated. Their model was successfully fitted against the infrared active frequencies, but shows marked differences to the Raman frequencies.…”
Section: Raman Spectroscopymentioning
confidence: 99%